In vitro and in vivo effects of sorghum condensed tannins encapsulated in kafirin microparticles on digestive amylases - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.